Distribution And Abundance Of Benthic Foraminifera In The Coastalwaters Around Penang National Park - Minhat, Fatin Izzati (2013)
A study on the distribution and abundance of benthic Foraminifera was conducted along the coastal waters of Penang National Park, Malaysia. Four selected sites (i.e Teluk Bahang, Teluk Aling, Teluk Ketapang and Pantai Acheh) were chosen based on the degree of anthropogenic activities. A total of 192 sediment samples were collected bimonthly between October 2010 and September 2011. Bulk sediments samples, water samples and environmental parameters were collected along the transect at 200 m intervals from the subtidal zone and extending up to 1200 m offshore. Foraminiferal assemblages comprised of 14 genera which include Ammonia, Elphidium, Ammobaculites, Nonionoides, Bolivina, Asterorotalia, Reophax, Eggerella, Textularia, Quinqueloculina, Astacolus, Lagena, Fissurina and Hopkinsina were identified. The stress-tolerant taxa, Ammonia (56.35 %) and Elphidium (9.11 %) dominated the assemblage at all sites. Meanwhile, the other functional groups (i.e. other smaller miliolids and agglutinated) which occurred <5% were considered as rare or accidental species. Diversity indices showed that Pantai Acheh has a diverse assemblage (H’ = 0.57) followed by Teluk Ketapang (H’ = 0.47), Teluk Bahang (H’ = 0.43) and Teluk Aling (H’= 0.35). Species assemblage indicated the anthropogenic effect on Foraminifera reduced with increase distance from the shore.